2015
DOI: 10.1117/12.2081887
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a statistical atlas of the radii of the optic nerve and cerebrospinal fluid sheath in young healthy adults

Abstract: Optic neuritis is a sudden inflammation of the optic nerve (ON) and is marked by pain on eye movement, and visual symptoms such as a decrease in visual acuity, color vision, contrast and visual field defects. The ON is closely linked with multiple sclerosis (MS) and patients have a 50% chance of developing MS within 15 years. Recent advances in multi-atlas segmentation methods have omitted volumetric assessment. In the past, measuring the size of the ON has been done by hand. We utilize a new method of automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…We have demonstrated that this pipeline is sufficiently accurate to detect local population changes in both ON and CSF sheath size. The results are consistent with previous results that population variability should not vary across individuals based on age or sex [17]. Previously ON biomarkers have been investigated using manual or semi-automated methods which measured the ON at arbitrary points along the ON [4, 18, 19].…”
Section: Discussionsupporting
confidence: 90%
“…We have demonstrated that this pipeline is sufficiently accurate to detect local population changes in both ON and CSF sheath size. The results are consistent with previous results that population variability should not vary across individuals based on age or sex [17]. Previously ON biomarkers have been investigated using manual or semi-automated methods which measured the ON at arbitrary points along the ON [4, 18, 19].…”
Section: Discussionsupporting
confidence: 90%
“…Our group has characterized these improvements in optic nerve MRI in healthy controls. 9 Additionally, we have recently developed an analysis pipeline for optic nerve MRI that affords an opportunity to evaluate the morphology of the optic nerve in vivo along its entire length, 10 , 11 thereby allowing measurements of both global and focal atrophy.
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
“…With a larger set of controls [10] evaluated with this method they could be compared against disease populations, such as acute optic neuritis or MS to investigate possible imaging biomarkers for disease severity or prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Automated segmentation methods have largely focused on segmenting the ON and CSF as a single structure, deeming it too challenging to measure the two independently [7, 8]. However, a previously presented slice-wise method addressed some of these concerns but yielded results which were useful in aggregate but could be difficult for interpretation on the single subject-level [9, 10]. Therefore, we propose a fully automated, three-dimensionally consistent technique, building upon the previous independent slice-wise technique, to estimate the radius of the ON and surrounding CSF on high-resolution heavily T2-weighted isotropic MRI.…”
Section: Introductionmentioning
confidence: 99%